2012
DOI: 10.3183/npprj-2012-27-02-p173-183
|View full text |Cite
|
Sign up to set email alerts
|

Flow conditions in the grooves of a Low-Consistency refiner

Abstract: The flow pattern in the grooves plays a major role for the homogeneity of refining as well as for the transfer and loading of fiber flocs in refining position on the bar edges. However, it is an area where very little information is available. In the present study, flow conditions in the grooves in a Low-Consistency (LC) - disc refiner were studied both experimentally and numerically. The experimental study involved high-speed imaging through a 3 cm peephole into a commercial refiner. The Computational Fluid D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…Due to its high importance in the paper-making industry, the eucalyptus pulp is considered in the present study. 1 The present results are also compared with those of softwood pulp in rotating and non-rotating grooves obtained by the Newtonian model proposed in Wittberg et al 11 Finally, the effect of variation in the groove geometry is investigated on the rotational motion of eucalyptus pulp within the rotating and non-rotating grooves.…”
Section: Introductionmentioning
confidence: 71%
“…Due to its high importance in the paper-making industry, the eucalyptus pulp is considered in the present study. 1 The present results are also compared with those of softwood pulp in rotating and non-rotating grooves obtained by the Newtonian model proposed in Wittberg et al 11 Finally, the effect of variation in the groove geometry is investigated on the rotational motion of eucalyptus pulp within the rotating and non-rotating grooves.…”
Section: Introductionmentioning
confidence: 71%
“…Earlier work has shown that there is internal recirculation in LC refiners that depend on the differential pressure over the refiner (Wittberg et al 2012). At high flow through the refiner, the outlet pressure was much lower, in the Braviken trial even lower than the feed pressure.…”
Section: Resultsmentioning
confidence: 96%
“…The case where G>0 is of interest because it represents a close geometrical similarity to that found in an LC refiner. Wittberg et al and Khohkar simulated a three‐dimensional cavity with an imposed pressure gradient along the cavity axis. The formation of multiple primary vortices under T/W ratios of 1.5 was observed, as in the case of G=0 above.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have focused on high-speed photography and describe the flow field qualitatively. [28,[33][34][35] For very dilute suspensions, Fox et al [36,37] reports found that the suspension flows inward in the stationary and outward in the moving cavities (see Figure 5). Minor recirculation currents, called secondary and tertiary flows, have also been observed.…”
Section: Introductionmentioning
confidence: 99%